THE EFFECTS OF L2 PRAGMATIC AUTONOMOUS AND CONTROLLED MOTIVATIONS ON ENGAGEMENT WITH PRAGMATIC ASPECT - Sanjaya, I Nyoman Suka; Sitawati, Anak Agung Raka; Suciani, Ni Ketut; Putra, I Made Ardana; Yudistira, Cokorda Gede Putra (TEFLIN Journal, 2022)
No study has investigated the relationship between student engagement per se and student motivation within second language (L2) pragmatics, notwithstanding the significance of engagement for L2 learning. The present study aimed to explore the effects of two global motivational orientations (autonomous and controlled motivations) on behavioral engagement within the perspective of L2 pragmatics by drawing on self-determination theory. A total of 76 college students agreed to participate and were requested to fill out a tailor-made, 34-item, 6-point Likert-scale questionnaire. The results of data analysis using standard multiple linear regression revealed that both Autonomous and Controlled Motivations significantly predicted and explained a large amount of variance in Engagement, F(2, 71) = 161.28, p < .01, R2 = .82, adjusted R2 = .81, and that the effect of Controlled Motivation, B = .33, t(71) = 8.05, p < .01, was twice as large as that of Autonomous Motivation, B = .16, t(71) = 4.91, p < .01. These findings indicate that students’ controlled motivation is more powerful in enhancing their engagement in learning L2 pragmatics. Pedagogically, it implies that teachers should bolster students’ motivation to learn L2 pragmatics, which can eventually lead to their increased engagement.